Cross-layer design in opportunistic spectrum access-based cognitive radio networks. (1st January 2012) - Foukalas, Fotis T.; Karetsos, George T.; Merakos, Lazaros F.
Cognitive radio is considered as one of the most important enablers for achieving enhanced spectral efficiency in wireless communications. In this work, we present a cross-layer design for reliable data transmission over a cognitive radio network which combines adaptive modulation at the physical layer and hybrid automatic repeat request at the data link layer. The cognitive radio network follows the principles of opportunistic spectrum access that utilises an optimal power adaptation policy for channel allocation. The obtained numerical results denote that the considered approach achieves significant spectral efficiency improvement and therefore it could be deployed in wireless communication networks that encompass cognitive capabilities. Furthermore, we assess the introduced interference and we show that it can be kept within levels that do not jeopardise our design.